Cyclic performance of I-beam-to-SHS column joint using through SMA bolts. (November 2022) - Chen, Zhenming; Gao, Fei; Wan, Shengbo; Wang, Zongyi; Huang, Shitao
Abstract: Shape memory alloys (SMAs) are increasingly used in steel structures. Three I-beam to square hollow section column joints with super-elastic SMA bolts were tested. A finite element model was subsequently developed, and a parametric study was conducted. The results show that all the joints can be classified as semi-rigid or partial-strength joints. With an increase in the SMA bolt length, the residual story drift and energy dissipation of the joint decreased. Increasing the SMA bolt diameter improved the energy dissipation capacity. In terms of energy dissipation and economic cost, installing the SMA bolts only outside the beam flanges is a good choice.